Construction of Quaternary Carbon Center via NHC Catalysis Initiated by an Intermolecular Heck-Type Alkyl Radical Addition - Su, Lanjun; Sun, Huan; Liu, Jikai; Wang, Chengming (Organic letters, 2021)
A quaternary carbon center containing an oxindole motif is constructed via NHC-catalyzed transition-metal and aldehyde-free intermolecular Heck-type alkyl radical addition initiated annulation. This redox-neutral protocol also features a simple procedure, broad substrate scope, good functional group tolerance and could be smoothly amplified to a gram scale. The mechanism study shows that the reaction possibly undergoes two folds of SET processes with an NHC radical cation intermediate involved.